Front Cover: Photochemistry at Scale: Wireless Light Emitters Drive Sustainability in Process Research & Development (Eur. J. Org. Chem. 5/2022). Issue 5 (1st February 2022) - Burek, Bastien O.; Duong, Hong Thu; Hochradel, Klaus; Sutor, Alexander; Rupp, Matthias; Heilmann, Eike K.; Lovis, Kai; Bloh, Jonathan Z.
Abstract : The Front Cover shows free‐moving wirelessly‐powered light emitters, which can be used to internally illuminate photochemical reactions. This enables easier scalability of reactions like the illustrated photoredox C–C coupling via Ir/Ni dual catalysis. More information can be found in the Communication by B. O. Burek, K. Lovis, J. Z. Bloh et al.